Price Determinants in the Global Emissions Trading Systems: A Systematic and Bibliometric Review - Chen, Yaolong; Latiff, Abdul Rais Abdul (International Journal of Energy Economics and Policy, 2025)
The Carbon Emissions Trading Price (CETP) is crucial in the Carbon Emissions Trading System (ETS). This study conducts a systematic and bibliometric review of 57 articles to explore the Determinants of Carbon Emissions Trading Price (DCETP) in global ETSs. The study revealed a substantial increase in the number of pertinent publications since 2018, driven by the expanding carbon market. China leads in contributions, although author collaboration is still limited. The analysis shows that energy factors are the most influential DCETP, while economic indicators, market policies, and environmental variables also play key roles. Methodologies are evolving, with recent research focusing on predictive models and advanced econometric techniques to address fluctuations in CETP. The research focus is shifting from the EU ETS to emerging markets such as China, highlighting the need for context-specific studies due to differences in the impacts of determinants across markets and models. This review integrates fragmented research, offering insights for policymakers and academics to optimize ETS design, enhance price stability, and support the low-carbon transition. Future research should prioritize new determinants, cross-market comparisons, and interdisciplinary theoretical integration.